2010
DOI: 10.3945/ajcn.2010.30185
|View full text |Cite
|
Sign up to set email alerts
|

Increased hepatic fat in overweight Hispanic youth influenced by interaction between genetic variation in PNPLA3 and high dietary carbohydrate and sugar consumption

Abstract: These findings suggest that Hispanic children carrying the GG genotype are susceptible to increased hepatic fat when dietary carbohydrate intake, specifically sugar, is high. Specific dietary interventions based on genetic predisposition in this population may lead to more effective therapeutic outcomes for fatty liver. This trial was registered at clinicaltrials.gov as NCT00697580, 195-1642394A1, and NCT00693511.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
160
2

Year Published

2011
2011
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 180 publications
(173 citation statements)
references
References 27 publications
(30 reference statements)
11
160
2
Order By: Relevance
“…This observation is likely multifactorial and may include a greater prevalence of the PNPLA3 gene, which is associated with higher liver fat content in the presence of dietary sugar (46) , higher overweight and obesity rates (6) , as well as higher abdominal obesity, consistent with prior findings among US adolescent and adult populations (47,48) . Our findings have a number of limitations.…”
Section: Discussionsupporting
confidence: 78%
“…This observation is likely multifactorial and may include a greater prevalence of the PNPLA3 gene, which is associated with higher liver fat content in the presence of dietary sugar (46) , higher overweight and obesity rates (6) , as well as higher abdominal obesity, consistent with prior findings among US adolescent and adult populations (47,48) . Our findings have a number of limitations.…”
Section: Discussionsupporting
confidence: 78%
“…This leads to development of macrovesicular steatosis ( 26,30 ), simple steatosis to steatohepatitis and progressive cirrhosis ( 31 ), and hepatic fi brinogenesis by a sterol regulatory element-binding protein (SREBP)-1c-PNPLA3 pathway ( 32 ). A greater impact of the L148M variant on hepatic lipid content is unmasked in the presence of other risk factors such as obesity ( 33 ), visceral adiposity ( 34 ), increased intake of sugars ( 35 ), omega-6 PUFAs ( 36 ), glucokinase regulatory protein gene variant ( 37 ), chronic hepatitis B ( 38 ), and hepatocellular carcinoma ( 39 ). In contrast to these reports, PNPLA3 has been reported to restore lipid homeostasis ( 40 ) by mediating acylation of lysophospholipids and hydrolyzing TGs in the liver in a direct manner or by regulation by cofactors ( 41,42 ).…”
mentioning
confidence: 99%
“…The relevance of this SNP in conferring human susceptibility to NASH and fibrosis progression has been shown in several studies as illustrated by an Italian study in 253 patients with NAFLD (28). Furthermore, it has been reported that the association between the I148M variant of PNPLA3 and serum levels of liver enzymes was associated with the size of the abdominal fat depot and high dietary carbohydrate and sugar consumption (29,30).…”
Section: Genetic Susceptibilitymentioning
confidence: 98%